Effect of activation ratio on the characteristics of AC derived from anaerobic digester residue and its applications in supercapacitors. Issue 9 (3rd February 2020) - Wu, Wentao; Zhang, Lele; Wang, Ce; Wang, Jin; Qian, Jiang; Song, Shaomin; Yue, Zhengbo
Abstract : Anaerobic digestion biogas residue contains a large amount of lignocellulose, and is a potential valuable biomass source. Abstract : Anaerobic digestion biogas residue contains a large amount of lignocellulose, and is a potential valuable biomass source. In the current study, activated carbon (AC) for supercapacitor electrodes was prepared with the anaerobic digestion residue collected from an anaerobic digester, with cow dung as the feedstock. The effects of activation ratio on the specific surface area, pore size distribution and electrochemical performance of AC were investigated. The results show that AC from the anaerobic digestion biogas residue could be used as a supercapacitor electrode material. The activated carbon obtained at the activation ratio of 3 has higher specific capacitance and good capacitance performance. The good electrochemical performance confirms that the anaerobic dry fermentation residue can be used as a good porous carbon electrode material for supercapacitors.